Mathematical Representation Ability in HOTS Problems : A Study of Students’ Learning Style - Febryana, Ultami Ismayani; Pradipta, Trisna Roy (Jurnal Paedagogy, 2025)
This study aims to analyze students’ ability to represent mathematical concepts when solving High Order Thinking Skills (HOTS) questions, reviewed based on visual, auditory, and kinesthetic learning styles. This study used a qualitative approach with a case study method with the subjects of nine students from SMAN 88 Jakarta who were selected by purposive sampling. The research instruments included learning style questionnaires, mathematical representation ability tests, and interviews. The data analysis technique in this study uses the stages of reduction, presentation, and drawing conclusions based on the Miles and Huberman model. The results of the study showed that all students, regardless of their learning style, mastered the visual aspect more. Learners with visual and auditory learning styles generally excel in visual aspects but weak in verbal and symbolic aspects, while learners with kinesthetic learning styles show varied abilities, with visual aspects remaining the most dominant. The findings of this study can provide insights for education practitioners to optimize mathematics learning based on students’ learning styles, while contributing theoretically to the development of academic theory and literature in the field of mathematics learning and mathematical representation.